Prince of Air - Hood, Ann, 1956- (The Treasure Chest, 2012)
Twins Felix and Maisie, along with their Great-Aunt Maisie and Great-Uncle Thorne, are transported back in time to Coney Island where they meet a young Harry Houdini.